18-pulse autotransformer rectifier unit using SEPIC converters for regulated DC-bus and high frequency isolation - Lourenco, Angelo C. (2015)
Multipulse rectifier topologies based on phase-shifting auto-connected transformers are increasingly applied in power electronics devices for power quality improvement. Due their construction, they mitigate many low-harmonic frequency and reduce the Total Harmonic Distortion of the line current (THDi), resulting a high Power Factor (PF). The 18-pulse topology is formed by a phase-shifting transformer or autotransformer and three six-pulse bridge rectifiers and, frequently, passives elements named Interphase Transformers (IPT's) are used to perform the DC outputs parallel connected. The delta-autotransformer topology, used in this work process approximately 20% of the total load. To reduce the bulky elements (IPT's) and to reach regulated DC-output, this work proposes using three SEPIC-based high-frequency isolated converters to link the DC-side of the bridges to the load. In addition, the secondary windings of these DC-DC converters can be connected in series or parallel to perform higher or lower voltage through the load. The laboratory prototype rating 2.4kW was built and the main simulation results are shown to confirm the high power factor, regulated DC-bus, and high-frequency isolation with reduced size and weight.